2021
DOI: 10.1136/sextrans-2021-055039
|View full text |Cite
|
Sign up to set email alerts
|

‘Stay at home …’: exploring the impact of the COVID-19 public health response on sexual behaviour and health service use among men who have sex with men: findings from a large online survey in the UK

Abstract: ObjectivesThe first UK national lockdown began on 23 March 2020, in response to the COVID-19 pandemic, and led to reduced STI/HIV service provision in the UK. We investigated sexual behaviour, use and need for sexual healthcare during the pandemic.MethodsParticipants (N=2018), including men (cis/transgender), transwomen and gender-diverse people reporting sex with another man (cis/transgender) or non-binary person assigned male at birth, completed an online cross-sectional survey (23 June 2020–14 July 2020), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
(20 reference statements)
2
17
0
1
Order By: Relevance
“…The study highlighted unmet need for SRH services, with one in 10 survey participants reporting unsuccessful attempts to access SRH services and one in five men needing but being unable to access condoms 12. Other UK studies found that men who have sex with men and young people experienced an unmet need for STI testing, contraception and condom access 13–15. This paper describes the results from qualitative follow-up interviews with Natsal-COVID participants exploring the experiences of unmet or delayed SRH need in the general population.…”
Section: Introductionmentioning
confidence: 97%
“…The study highlighted unmet need for SRH services, with one in 10 survey participants reporting unsuccessful attempts to access SRH services and one in five men needing but being unable to access condoms 12. Other UK studies found that men who have sex with men and young people experienced an unmet need for STI testing, contraception and condom access 13–15. This paper describes the results from qualitative follow-up interviews with Natsal-COVID participants exploring the experiences of unmet or delayed SRH need in the general population.…”
Section: Introductionmentioning
confidence: 97%
“…2 Consequently, sexual health services (SHS) rapidly reconfigured: in-person asymptomatic screening and walk-in appointments were suspended and patients directed online. 3 While the introduction of social restrictions during the first national lockdown 4 5 led to reductions in sexual risk behaviours for MSM (eg, one UK study of MSM found 47% reported new recent sex partners March-June/July 2020, a substantial decrease from 71% in a comparative 2017 sample), 6 they continued to be reported by a high proportion. [6][7][8] Social restrictions eased July-September 2020, 9 and sexual risk behaviour among MSM seemed to increase compared with the first national lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…1 During the COVID-19 pandemic, online surveys of MSM were carried out in the UK within the Reducing Inequalities and Improving Sexual Health (RiiSH-COVID) study. 2 The second survey ( 23November -12 December 2020) included questions on STI prophylaxis. The survey had 1,522 respondents, of which 1,520 completed the STI prophylaxis questions.…”
Section: Competing Interests: None Declaredmentioning
confidence: 99%
“…During the COVID-19 pandemic, online surveys of men-who-have-sex-with-men(MSM) were carried out in the UK within the Reducing Inequalities and Improving Sexual Health Study 2. The second survey (23 November–12 December 2020) included questions on STI prophylaxis.…”
mentioning
confidence: 99%